Single Molecule Study of the Polymerization of RecA on dsDNA: The Dynamics of Individual Domains - Maman, Nitzan; Kumar, Pramod; Yadav, Amarjeet; Feingold, Mario (Frontiers in Molecular Biosciences, 2021)
In the Escherichia coli, RecA plays a central role in the recombination and repair of the DNA. For homologous recombination, RecA binds to ssDNA forming a nucleoprotein filament. The RecA-ssDNA filament searches for a homologous sequence on a dsDNA and, subsequently, RecA mediates strand exchange between the ssDNA and the dsDNA. In vitro, RecA binds to both ssDNA and dsDNA. Despite a wide range of studies of the polymerization of RecA on dsDNA, both at the single molecule level and by means of biochemical methods, important aspects of this process are still awaiting a better understanding. Specifically, a detailed, quantitative description of the nucleation and growth dynamics of the RecA-dsDNA filaments is still lacking. Here, we use Optical Tweezers together with a single molecule analysis approach to measure the structure of the individual RecA domains on dsDNA and the corresponding growth rates for each of their fronts. We focus on the regime where the nucleation and growth rate constants, kn and kg , are comparable, leading to a coverage of the dsDNA molecule that consists of a small number of RecA domains. For the case of irreversible binding (using ATPgammaS instead of ATP), we find that domain growth is highly asymmetric with a ratio of about 10:1 between the fast and slow fronts growth rates.